Pengaruh Model Outdoor Learning Terhadap Keterampilan Menulis Puisi Siswa SD Negeri 6 Rambang - Aprila, Kiki; Destiniar , Destiniar; Mega Prasrihamni, Mega Prasrihamni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to find out whether or not the influence of outdoor learning models on the poetry writing skills of students of State Elementary School 6 Rambang. Merode research used is a quantitative method with data collection techniques that are deed tests. The method used in the study was outdoor learning, with posstest-only control design used to determine the effect of a treatment of the study subject. The population of this study is a student of grade IV Of State Elementary School 6 Rambang which consists of two classes with a total of 30 students. Class IVA as an experimental class of 15 peopleand class IVB as a control class with 15 students. Based on the results and discussion and calculation of data with significant levels (α) 0.05 and dk = 15-1 = 14. Thitung = 4.6 can thus conclude thitung>ttabel or 4.6 > 1.761, then H0 is rejected and Ha is accepted. It can be concluded that this hypothesis states that research has a significant influence in the use of outdoor learning models on the poetry writing skills of elementary school students.